IDENTIFICATION OF GROUPER (EPINEPHELUS SP) AT MUARA ANGKE TRADITIONAL FISH MARKET IN NORTH JAKARTA USING MORPHOLOGY AND DNA BARCODING METHODS - Shodikin Aznardi; Hawis Madduppa (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
Grouper fish is the most exploited commodity for coral fisheries. The controversy that occurred between researchers regarding the identification of fish species is a problem that is quite alarming. Identification using morphometric measurements, shape and color or morphology is considered still not accurate in determining the fish species. The DNA barcoding method uses COI markers by tracing the nucleotide bases to determine which species of biota have advantages in species identification. This study aims to identify grouper fish species in the traditional Muara angke fish market by using morphological methods and DNA barcoding. The identification results obtained from the morphological methods (shape, color and morphometrics) that the sample species are white-tailed grouper fish (Epinephelus areolatus) by looking at morphological characteristics, namely the white lines on the caudal fins and brown spots on the body. Identification using the DNA Barcoding method using the COI markers showed that the fish samples were 95% similar to E. areolatus.